Seasonal influenza vaccine uptake and vaccine refusal among pregnant women in France: results from a national survey. Issue 5 (3rd May 2020) - Descamps, Alexandre; Launay, Odile; Bonnet, Camille; Blondel, Béatrice
ABSTRACT: Pregnant women and infants are at high risk for severe influenza and many countries, including France, recommend annual influenza immunization during pregnancy. We aimed to estimate influenza vaccination and refusal rates and assess associated factors among pregnant women during the 2015–16 season in France. We used data from a national representative sample of women who gave birth in March 2016 and were interviewed before hospital discharge (N = 11, 752). In the multivariable analysis, robust Poisson regression models were used to study associations with maternal characteristics and prenatal care characteristics. Influenza vaccine coverage among pregnant women was 7.4% (95% confidence interval [CI]: 6.9–7.9). Only 24.9% (95% CI: 24.2–25.7) of women said that they received a care provider proposal for vaccination and 70.4% (95% CI: 68.7–72.0) of these declined it. Vaccine uptake was associated with low parity (prevalence ratio [PR] = 2.1; 95% CI: 1.4–3.2 for parity 0 vs ≥ 3), high educational level (PR = 2.5; 95% CI: 2.0–3.2), healthcare occupation during pregnancy (PR = 1.8; 95% CI: 1.5–2.1) and preexisting conditions at risk for influenza (PR = 1.7; 95% CI: 1.3–2.2). Women were more frequently vaccinated when their main care provider was a general practitioner. Multiparae women and those with medium or low educational level were significantly more likely than others to decline influenza vaccine after a provider proposal. Influenza vaccine coverage is very low in France, mainly because of infrequent care provider proposals and also frequent women's refusals. Effective interventions should be designed to promote vaccination among medical professionals and reduce vaccine hesitancy among pregnant women.